Evaluating the functionality of xeno‐relevant transgenes. (March 2014) - Baehr, Andrea; Wuensch, Annegret; Kemter, Elisabeth; Kessler, Barbara; Kurome, Mayuko; Seissler, Jochen; Ayares, David; Wolf, Eckhard; Klymiuk, Nikolai
<x xml:space="preserve">Abstract</x> With the scientific progress made in recent years, clinical application of xenotransplantation has become a realistic goal. Besides optimizing immunosuppressive regimens, the development of geneticallytailored donor pigs contributed to this success. Within the CRC 127 "Biology of xenogeneic cell, tissue and organ transplantation – from bench to bedside" we aim at developing novel transgenic donor pigs for islet transplantation, and providing existing transgenic donor lines to German as well as international collaboration partners. Regarding novel donor models, we have established transgenic pigs carrying the x‐linked inhibitor of apoptosis (XIAP) under the control of the porcine insulin promoter to achieve beta‐cell specific expression, as apoptosis has been postulated to play a major role in islet loss during isolation, in vitro cultivation and engraftment. Expression analyses of the first transgenic founders are presently underway. In addition, an advanced donor pig aiming at the temporary expression of vascular endothelial growth factor (VEGF) for improved engraftment of islets is being established. The model is based on the TetOn principle which requires two independent transgenes. First litters of founder pigs carrying a construct for beta‐cell specific expression of the transactivator (TA) have been delivered and qPCR analysis of the pancreas revealed different levels of TA expression in individual animals. Primary cells from a highly expressing founder will be transfected with a construct carrying the regulated VEGF gene under the control of the TA response element. For detailed pre‐clinical evaluation of already characterized transgenic pigs, we have established multitransgenic lines in collaboration with Revivicor Inc. carrying either aGalTKO/CD46/hTM, aGalTKO/CD46/INS‐LEA or aGalTKO/CD46/HLA‐E. We provide these animals, in addition to single‐transgenic INS‐LEA pigs, to the groups of P.Brenner and J.Seissler within the consortium. Furthermore, multi‐transgenic animals are provided to the groups of M.Mohiuddin, D.K.C. Cooper and R. Pierson by D. Ayares and islets of INS‐LEA expressing pigs are supplied to B. Hering in collaboration with J. Seissler. The ongoing evaluation of existing transgenes or their combination will reveal more detailed insight into the complexity of rejection mechanisms and, thus, support the design of optimized future transgenic approaches.